PERAN IBU PEKERJA (WANITA KARIER) DALAM MEMBENTUK KARAKTER KEAGAMAAN ANAK DI DUSUN NGADIPURO KECAMATAN TUTUR KABUPATEN PASURUAN - Nicho Desvian Pratama; Mohammad Afifulloh; Imam Safi’i (VICRATINA, 2020)
This study provides an explanation of the role of working mothers (career women) in shaping the religious character of children in Ngadipuro Hamlet, Tutur Subdistrict, Pasuruan Regency. The research is phenomenological with a qualitative approach. This study aims to determine the role of working mothers in shaping the religious character of Ngadipuro Hamlet in Tutur Subdistrict, Pasuruan Regency. To find out the strategies, inhibiting factors, and supporting working mothers in shaping religious character children Ngadipuro Hamlet, Tutur Subdistrict, Pasuruan Regency. To obtain data, researchers used three methods through interviews with informants, field observations, and other supporting documentation. The data obtained were then analyzed using three stages namely data reduction, data presentation, and data inference. Then the working mother in this hamlet has a strategy in shaping the religious character of children through a habituation approach, being kind to children, and rational teaching. The inhibiting factors in shaping the religious character of children in Ngadipuro hamlet are divided into two internal factors related to the lack of knowledge and understanding of the second mother's religion, external factors related to the influence of large gadgets, busy activities that forget worship and weak economic conditions. While the supporting factors are motivation and self-encouragement owned by children and the child's life picture as a successor to parents.